Isaac on Jewish and Christian altars: polemic and exegesis in Rashi and the Glossa ordinaria - Schoenfeld, Devorah (Fordham series in medieval studies, 2013)
The developing Jewish-Christian polemic -- Rashi and his sources -- The sources and manuscript evolution of the Glossa ordinaria on Genesis 22 -- Isaac on Jewish and Christian altars: polemic, faith, and sacrifice in Rashi and the Gloss on Genesis 22 -- Appendixes: A critical edition of the Glossa ordinaria on Genesis 22: 1,19 -- Major manuscript variants in Rashi's commentary on Genesis 22